Customer satisfaction toward Sahabat EON program / Mohd Redza Nizam Radzuan - Radzuan, Mohd Redza Nizam (Faculty of Business and Management, 2008)
The purpose of this research is to study the customer's satisfaction towards Sahabat EON Program (SEP) provided by Edaran Otomobil Nasional Berhad (EON) in Glenmarie, Shah Alam Selangor and the relationship between customer service, service quality, and image with the customer satisfaction. Moreover, this study will identify the problem causes in SEP and examine the relationship of the variables items that will influence the satisfaction with the service provided in order to enhance and gain more satisfaction among the customers. The findings showed that most of the customers were satisfied with EON's image provided to them and also the customer service. However, the service qualities provided by SEP have weak relationship with the customer's satisfaction. The researcher is also able to give some recommendations and suggestions on how to improve and increase customer's satisfaction after the analysis and interpretation data. In this study, we used interviews and questionnaire techniques for data collection. Based on frequency table including means, mode and standard deviations, a clear findings and result is observed.